The importance of correct implants positioning and masticatory load direction on a fixed prosthesis - Tribst, João-Paulo-Mendes [UNESP]; Rodrigues, Vinicius-Aneas [UNESP]; Dal Piva, Amanda-Maria-de Oliveira [UNESP]; Borges, Alexandre-Luiz-Souto [UNESP]; Nishioka, Renato-Sussumo [UNESP] (Medicina Oral, S.L., 2018)
Background: Through the biomechanical study of dental implants, it is possible to understand the dissipation effects of masticatory loads in different situations and prevent the longevity of osseointegration. Aims: To evaluate the microstrains generated around external hexagon implants, using axial and non-axial loads in a fixed four-element prosthesis with straight implants and implants inclined at 17°. Material and Methods: Three implants were modeled using CAD software following the manufacturer's measurements. Then, implants were duplicated and divided into two groups: one with straight implants and respective abutments, and the other with angled implants at 17° and respective abutments. Both groups were arranged inside a block simulating bone tissue. A simplified fixed prosthesis was installed on both groups and the geometries were exported to CAE software. Five loads of 300N were performed at axial and non-axial points on the fixed prosthesis. Stress on the implants and strain on the block were both analyzed. An in vitro experiment was performed following all structures made in FEA in order to validate the model. In each experimental block, 4 strain gauges were linearly placed between the implants and the same loads were repeated with a loading applicator device. Results: The deformations computed by the gauges were correlated with the FEA results, showing that the group with inclined implants had more damaging biomechanical behavior and was significantly different from the group with straight implants (P < 0.005). Conclusions: The mathematical model used is valid and inclined implants can induce unwanted bone remodeling.
Keywords: Child; Dental caries; Health Services Accessibility; Poverty